Combustion Characteristics of Coal-Water Slurry Droplets in High-Temperature Air with the Addition of Syngas; Energies; Vol. 16, iss. 8 - Belonogov M. V. Maxim Vladimirovich; Dorokhov V. V. Vadim Valerjevich; Glushkov D. O. Dmitry Olegovich; Kuznechenkova D. A. Darjya Antonovna; Romanov D. S. Daniil Sergeevich (2023, 2023)
Title screen